The village-owned enterprise in the Context of the Villagers’ Welfare - Kamil, Muhammad Ikhsan; Isnani, Atin Meriati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Village-owned enterprises is an important entity in the Indonesian democratic economic system that aims to improve the well-being of the villagers. The economic democratic system in the village refers to the principle that the village economy is managed and planned by the villagers in accordance with their potential, on the basis of family and royong gotong. The research emphasizes that Village-owned enterprises was established to accommodate all economic and public service activities managed by the village or inter-village cooperation, in accordance with Government Regulation No. 11 Year 2021. The main objective of Village-owned enterprises is to increase the prosperity of the people of the village through economic independence and the application of the principles of economic democracy. As a legal body, Village-owned enterprises, is expected to comply with applicable regulations and laws with high transparency and accountability, as well as ensuring the sustainability of programs that benefit the village community. Public participation in decision-making is also the key to achieving shared happiness and well-being. Philosophically, Village-owned enterprises should be able to fill the void in village development and not replace existing economic activity. With professional management and integration into local and national economic systems, Village-owned enterprises is expected to improve the well-being of the villagers sustainably